Analisis Manajemen Pada Pemanfaatan Dana Mushola Jauharul Wathan Rt. 07 Kelurahan Mayang Mangurai - MS Rahmat; Maulana Yusuf; Jevi Saputra (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2024)
This research aims to analyze management in the utilization of funds from the Jauharul Wathan Prayer Room in the RT. 07 Mayang Mangurai Village. Research was conducted to understand how these funds are managed and used to support religious and social activities in the environment. The method used is a case study with a qualitative approach through in-depth interviews and direct observation of the fund management process. The research results show that the management of the funds of the Jauharul Wathan Prayer Room is influenced by factors such as transparency, accountability and community participation in decision making. The implication of this research is the importance of improving fund governance to ensure better efficiency and effectiveness in the use of funds.